Utilization of carrageenan-based edible coating for the browning inhibition of minimally processed bananas (Musa bal bisiana) - Enage, Ana Margarita T.; Rumbaoa, Rowena Grace O. (Quezon City College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT Fresh-cut produce are prone to deteriorative changes caused by enzymatic actions, one of which is called enzymatic browning. The objective of the study was to utilize carrageenan-based edible coating to inhibit browning reactions in minimally processed bananas. Visual Quality Rating (VQR) was employed to observe the browning behavior of fresh-cut bananas treated with different edible coating systems. Edible coating solution containing 0.5% carrageenan and 0.5% citric acid provided the best result in VQR. Kinetics of enzymatic browning was determined using color development measured by the Hunter Lab colorimeter. Browning of the treated and untreated bananas followed first-order kinetics. The selected edible coating was standardized using the following parameters: pH, TA, TSS, weight reduction, and color change. No significant difference (P>0.05) was found among the runs for each parameter, indicating repeatability of the process, except for the discrepancy found in the L* and a* values. DMRT showed that the L* and a* value on the third run was significantly different from the first two runs. However, directly perceived intensity of browning in terms of VQR did not show any significant difference for the three runs which may imply that this discrepancy was not visually recognized. The prepared carrageenan-based edible coating did not completely suppress enzyme activity, but it was proven to effectively slow down browning reactions in minimally processed bananas.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Bananas; Carrageenan; Edible coating